2011
DOI: 10.1159/000331401
|View full text |Cite
|
Sign up to set email alerts
|

Arthrogryposis Multiplex Congenita and Pena-Shokeir Phenotype: Challenge of Prenatal Diagnosis – Report of 21 Cases, Antenatal Findings and Review

Abstract: Objective: To elaborate the antenatal sonographic findings of fetuses with the suspicion of fetal akinesia, thereby focusing on the accuracy of prenatal differentiation between subtypes of fetal akinesia, namely Pena-Shokeir phenotype (PSP) and arthrogryposis multiplex congenita (AMC). Methods: We herein present our experience of 21 patients with PSP and AMC diagnosed antenatally at a tertiary prenatal referral center. During the study period 30,485 consecutive high- and low-risk pregnancies were examined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 49 publications
2
37
1
Order By: Relevance
“…Antenatally or perinatally, lethal disorders mostly manifest early in pregnancy from the first trimester onwards. Lethal forms show early lung hypoplasia (and later thoracic hypoplasia), or pterygia . Reduced fetal breathing may be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antenatally or perinatally, lethal disorders mostly manifest early in pregnancy from the first trimester onwards. Lethal forms show early lung hypoplasia (and later thoracic hypoplasia), or pterygia . Reduced fetal breathing may be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding skeletal muscle proteins, involved in tissue and structural development and differentiation as well as contraction processes [58][59][60][61] or pterygia. 62 Reduced fetal breathing may be observed.…”
Section: Gene Symbol (Hgnc) Accession Refseq Chromosomal Region Condimentioning
confidence: 99%
“…Most of our cases did not show these latter features since the pregnancy was often terminated before 24 weeks of gestation. The second case series on antenatal findings in 21 cases with AMC and FADS examined between 12–30 weeks gestational age suggested that pulmonary hypoplasia is obligatory in FADS and cannot be found in AMC . When pulmonary hypoplasia was found, the pregnancy was terminated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited serial motor assessments demonstrated which reduced activity, is a late expression of affected motor activity and possibly not initiating the contractures . Though different authors advise evaluation of the fetal motility, until now, the main focus has been on diagnosing the different structural anomalies known to occur with FADS …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation